PENGEMBANGAN E-BOOKLET KEANEKARAGAMAN JENIS TUMBUHAN OBAT PADA EKOSISTEM RAWA GAMBUT BERBASIS STEM DI TEMBILAHAN HULU - Laila, Rosita; Suwondo; Wahyuni, Resma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the diversity of medicinal plant species in peat swamp ecosystems in Tembilahan Hulu, Indragiri Hilir Regency, and to analyze the validity of a STEM-based e-booklet as a biology learning medium for senior high school students. The research was conducted from February to April 2026 in three villages: Pulau Palas, Pekan Kamis, and Sialang Panjang, Tembilahan Hulu District. This study employed a cruise method for medicinal plant inventory, ethnobotanical interviews with ten community informants, and the ADDIE model for e-booklet development. The results identified 47 medicinal plant species from 28 families, with Lamiaceae (5 species) and Zingiberaceae (4 species) as the most dominant families. The Shannon-Wiener diversity index (H') was highest in Station II (home gardens) at 3.562, followed by Station III (plantations) at 3.125, and Station I (shrubland) at 2.691. Leaves were the most commonly used plant part (57.4%), boiling was the dominant processing method (72.3%), and oral consumption was the primary usage method (87.2%). Medicinal plants were utilized across ten organ system groups, with metabolism and antioxidants as the largest group (23 species). The STEM-based e-booklet received an overall validation score of 3.53, categorized as very valid, across five assessed aspects, namely format and graphics (3.63), illustrations and images (3.56), language (3.50), content feasibility (3.50), and STEM integration (3.47), and was declared suitable for use with revisions